New Imidazole Inhibitors of Mycobacterial FtsZ: the Way from High-Throughput Molecular Screening in Grid up to in vitro Verification - Karpov, P.A.; Demchuk, O.M.; Brytsun, V.M.; Lytvyn, D.I.; Pydiura, N.O.; Rayevsky, A.V.; Samofalova, D.A.; Spivak, S.I.; Volochnyuk, D.M.; Yemets, A.I.; Blume, Ya.B. (Science and Innovation, 2024)
Within the framework of virtual organization CSLabGrid, high-throughput molecular screening has been performed for new antituberculosis compounds. Using the FlexX program installed on the Institute of Food Biotechnology and Genomics (IFBG) Cluster and models of four promising ligand binding sites on the surface of FtsZ protein from Mycobacterium tuberculosis, virtual screening has been done for the database containing 2886 compounds synthesized in the Institute of Organic Chemistry of the NAS of Ukraine. Based on the LE and ΔG scores, the docking scores of CCDC Gold, and the results of molecular dynamics, a group of Mycobacterial FtsZ inhibitors has been selected. In vitro validation have revealed 6 compounds with the highest inhibition of GTPase activity of FtsZ. Also, based on in vitro experiment, three of selected compounds demonstrste strong inhibition of FtsZ polymerization together with inhibition of its GTPase activity.